EFL students’ deadlock in argumentative writing: Voices in gender perspective - Juhana, Juhana; Sundari, Hanna; Pratiwi, Widya Rizky (Jurnal Cakrawala Pendidikan, 2023)
Writing difficulty and constraints have gained much attention nowadays, particularly in the EFL context. However, the writing difficulties of EFL male and female writers perceived in developing an argumentative essay were still under-researched. To fill the void, this concurrent mixed method study aimed to scrutinize the variation and frequency and explore the perceptions of being argumentative writers among 113 EFL university students in Jakarta, Indonesia. Online questionnaires were distributed through a survey and the framework of interpretative phenomenological analysis (IPA), and the interviews were conducted concurrently. The findings illustrated that EFL male and female writers experienced almost similar major difficulties, including argumentative text genre, language use, difficulty in source/reference, problems in the cognitive process, and other technical difficulties. Further, to be argumentative writers, female writers tend to feel various combinations of feelings and apply more learning strategies. In contrast, male writers express more on the cognitive process of essay completion. However, either male or female writers become more aware of their weaknesses in the English language, such as reading skills.